Adolf Loos works and projects - Bock, Ralf 1965- (Skira, 2021)
In this definitive monograph, a true labor of love, architect Ralf Bock seeks to reveal the sensuality of Loos' interior designs, focusing on his sincere belief in the evolution of tradition. The book explores 30 existing projects from Loos' oeuvre, documented in 160 full-color images by the celebrated French photographer Phillippe Ruault. Along with materials from the Loos archive at the Albertina Museum Vienna, these photographs and Bock's commentary provide a new interpretation of Loos' work and encourage the reintroduction of his ideology into the contemporary architectural conversation. Profiles of Loos' original clients and interviews with people who currently inhabit his designs round out this unique publication
"First published in Itlay in 2007 by Skira Editore" -- colophon
Keywords: Loos, Adolf -- 1870-1933; Architektur; Loos, Adolf / 1870-1933 / Criticism and interpretation; Architect / Austria / Biography; Criticism, interpretation, etc